Seismic monitoring and verification for the Co2CRC Ottway Basin project - Urosevic, Milovan; Campbell, A; Dahlhaus, L; Gendrin, A; Leaney, W; Tcherkashnev, S; Verliac, M (Elseveir, 2008)
The Otway Project conducted under the Australian Cooperative Research Centre for Greenhouse Gas Technologies (CO2CRC) is the first of its kind, where CO2 is injected into a depleted gas reservoir. The use of depleted fields for CO2 storage is likely to become widely adopted globally and, therefore, the project will provide important experience for monitoring under these conditions. However, such scenario is not favorable for the application of geophysical techniques for the purpose of CO2 monitoring and verification (M&V) because the injection of CO2 into a CH4 depleted reservoir is modeled to produce very subtle changes in elastic properties of the reservoir rock which may be very difficult to measure. Consequently geophysical program for the Otway site was design according to the expected time-lapse effects. It combines both surface and borehole seismic methods. Surface seismic should provide a global vision of the underground and an indirect confirmation of the CO2 containment by recording no differences between the successive time-lapse experiments. Vertical Seismic Profile (VSP) surveys are expected to provide an improved characterization of the reservoir and hopefully a direct indication of the fluid distribution and/or its potential upward migration along the reservoir bounding fault pattern. Indeed the results of the current analysis of both pre-base line (test) and base-line 2D and 3D VSP data are encouraging. The availability of vector wave field (three-component) data recorded in VSP surveys should significantly improve the outcomes of M&V program at Naylor site.